PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI SULAWESI SELATAN - Hendra Gunawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effect of work environment and work motivation on employee performance, both directly and indirectly through service quality at the Population and Civil Registration Office of South Sulawesi Province. This study employed a quantitative approach with an explanatory research design. The sample consisted of 93 employees. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The results show that work environment has a positive and significant effect on service quality and employee performance. Work motivation also has a positive and significant effect on service quality and employee performance. Furthermore, service quality has a positive and significant effect on employee performance. The mediation test confirms that service quality significantly mediates the effect of work environment and work motivation on employee performance. These findings indicate that improving employee performance in population administration services is not only determined by a supportive work environment and employee motivation, but also by the organization's ability to translate these factors into fast, accurate, responsive, and citizen-oriented services.